Enhancing the recovery of human-edible nutrients in milk and nitrogen efficiency throughout the lactation cycle by feeding fatty acid supplements - de Souza, Jonas; Batistel, Fernanda; Santos, Flávio Augusto Portela (Frontiers in Sustainable Food Systems, 2023)
Dairy cows convert low-quality feedstuffs unsuitable for human consumption into milk, a high-quality protein source for humans. Even under grazing conditions of well-managed pastures, dietary energy limits the efficiency of animal production, contributing to the excretion of nutrients to the environment. Thus, our study aimed to assess the effect of supplying sources and levels of supplemental fat to grazing dairy cows during early lactation on nutrient excretion and recovery of human-edible (HE) nutrients in milk throughout the lactation cycle. Two experiments were conducted with grazing Jersey × Holstein dairy cows. In Experiment 1, five dairy cows were used in a 5 × 5 Latin Square design. Treatments were a control diet (concentrate without supplemental fat) or diets supplemented with calcium salts of either soybean fatty acids (CSSO) or palm fatty acids (CSPO) fed at two levels of supplementation (400 g/day or 700 g/day) for 24 days. In general, the level of supplemental fat had a minor effect on production parameters and methane emission and intensity. Feeding cows with CSPO increased milk yield by 8.1%, milk energy output by 20%, and milk fat yield by 35.2% compared with CSSO. A tendency was observed for CSPO to decrease methane per unit of milk energy compared with CSSO. In experiment 2, 24 dairy cows were used in a randomized block design. Treatments were a control diet or diets supplemented with calcium salts of either CSSO or CSPO fed at 400 g/day for 13 weeks. The carryover effect of the diets was evaluated until 42 weeks of lactation. During the supplementation period, feeding CSPO improved the recovery of HE energy, protein, and indispensable amino acids compared with control and CSSO. Interestingly, we demonstrated that feeding CSPO improved the recovery of HE energy, protein, and indispensable amino acids compared with control over the lactation cycle. Overall, our results suggested that the dose of supplemental fat used in our study had a minor influence on production and rumen fermentation parameters. We demonstrated that feeding dairy cows with a fatty acid source based on palm oil under tropical grazing conditions reduced nutrient excretion and improved the recovery of HE nutrients throughout the lactation cycle.